The influence of sport participation and parental involvement on alcohol consumption amongst Icelandic adolescents - Ari Friðfinnsson 1996- (2020)
The aim of this study was to examine the relationship between sport participation, organized and unorganized, and parent‘s involvement and alcohol consumption amongst Icelandic adolescents. Three hypothesis were tested. A cross-sectional self-report study, Youth in Iceland, was used with a sample size of 2106 Icelandic students in 8th to 10th grade in all secondary schools, 48.1% males and 50.7% females. Binary logistic regression was used for data analysis. Participating in unorganized sports is not associated with alcohol. However, participating in organized sports is associated with less likelihood of the Icelandic adolescent having ever been drunk. Icelandic adolescents who participate in organized sports and have their parents involved is associated with less likelihood of the Icelandic adolescent having ever been drunk. Future research should examine cultural differences when it comes to social organization of organized sports. Also, should focus on engaging parents who are not involved in their childrens organized sports activities. More varied choices of organized sports to reach out to more children and parents to increase participation should be discussed. Keywords: adolescents, alcohol consumption, sports, parents Útdráttur Þessi rannsókn rannsakar tengsl skipulagðra og óskipulagðra íþróttaþátttöku, ásamt þátttöku foreldra og áfengisneyslu ungmenna, Notast var við gagnasafn úr þversniðsrannsókninni Ungt fólk. Notast var við úrtak af 2106 nemendum í 8 - 10 bekk úr öllum grunnskólum á Íslandi 48,1% strákar og 50,7% stelpur. Aðhvarfsgreining var notuð við úrvinnslu gagna. Þátttaka í óskipulögðu íþróttastarfi hefur engin tengsl við áfengi. Hinsvegar, er þátttaka í skipulagðri íþróttastarfsemi fyrirbyggjandi þáttur þegar kemur að áfengisneyslu ungmenna. Það skiptir sköpum að foreldrar taki einnig þátt í skipulögðu íþróttastarfi barnanna sinna. Því að þau ungmenni sem stunda skipulagða íþróttastarfsemi og eru með foreldra sem taka þátt því meiri líkur eru á því að unglingurinn hefur ekki drukkið. ...